The composite face illusion: A whole window into our understanding of holistic face perception - Rossion, Bruno (Visual cognition, 2013)
Two identical top halves of a face are perceived as being different when their bottom halves belong to different faces, showing that the parts of a face cannot be perceived independently from the whole face. When this visual illusion is inserted in a matching task, observers make more mistakes and/or are slower at matching identical top face halves aligned with different bottom halves than when the bottom halves are spatially offset: The composite face effect. This composite face paradigm has been used in more than 60 studies that have provided information about the specificity and nature of perceptual integration between facial parts ("holistic face perception"), the impairment of this process in acquired prosopagnosia, its developmental course, temporal dynamics, and neural basis. Following a review of the main contributions made with the paradigm, I explain its rationale and strengths, and discuss its methodological parameters, making a number of proposals for its optimal use and refinement in order to improve our understanding of holistic face perception. Finally, I explain how this standard composite face paradigm is fundamentally different than the application to facial parts of a congruency/interference paradigm that has a long tradition in experimental psychology since Stroop (1935), and which was originally developed to measure attentional and response interference between different representations rather than perceptual integration. Moreover, a version of this congruency/interference paradigm used extensively over the past years with composite faces lacks a baseline measure and has decisional, attentional, and stimulus confounds, making the findings of these studies impossible to interpret in terms of holistic perception. I conclude by encouraging researchers in this field to concentrate fully on the standard composite face paradigm, gaze contingency, and other behavioural measures that can help us take one of the most important challenges of visual perception research: Understanding the neural mechanisms of holistic face perception.